Increased Absorption with Al Nanoparticle at Front Surface of Thin Film Silicon Solar Cell - Mukti, Rokeya Jahan; Hossain, Md Rabiul; Islam, Ariful; Mekhilef, Saad; Horan, Ben (MDPI, 2019)
This article presents an effective structural design arrangement for light trapping in the front surface of a thin film silicon solar cell (TFSC). Front surface light trapping rate is significantly enhanced here by incorporating the Aluminium (Al) nanoparticle arrays into silicon nitride anti-reflection layer. The light trapping capability of these arrays is extensively analyzed via Finite Difference Time Domain (FDTD) method considering the wavelength ranging from 400 to 1100 nm. The outcome indicates that the structural parameters associated with the aluminium nanoparticle arrays like particle radii and separations between adjacent particles, play vital roles in designing the solar cell to achieve better light trapping efficiency. A detailed comparative analysis has justified the effectiveness of this approach while contrasting the results found with commonly used silver nanoparticle arrays at the front surface of the cell. Because of the surface plasmon excitation, lower light reflectance, and significant near field enhancement, aluminium nanoparticle arrays offer broadband light absorption by the cell. © 2019 by the authors.